Magnet: exposing abusive relationships with interactive narrative - da Silva, Natalia Pinheiro; Jang, Jenifer de Jesus; Amaral, Vinicius Oliveira (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS), 2020)
This article is part of a non-finished project whose aim is to highlight the importance and the impact of using interactive narratives to expose and provoke reflection on social issues, and, conjointly, to present the concept of Magnet, an interactive game in development that features a female main character who is trapped in an abusive relationship, approaching the circumstances surrounding this matter.